Enfant terrible, або “Інший” посеред більшості (Ігор Костецький. На шляху до української моделі модернізму) - Барабаш, Ю. (Слово і Час, 2018)
Простежується шлях перетворення російськомовного літератора-початківця Ігоря Мерзлякова у визнаного в європейському літературному світі українського письменника Ігоря Костецького. Подано аналіз висунутої Костецьким у співдоповіді на з’їзді МУРу 1945 р. концепції “українського реалізму ХХ сторіччя” – “псевдоніма” української моделі модернізму, з якою пов'язалася його репутація enfant terrible української літературної еміґрації, також екзистенціальних ідей, проблеми двійництва, системи модерністичних засобів поетики в оповіданнях і п'єсах Костецького. The article follows the tortuous way of spiritual and creative transformation of a Russian-writing beginner, a literature failure Igor Merzlyakov into Ihor Kostetskyi, the Ukrainian prosaist, playwright and essayist acknowledged in European literary world, the correspondent of Western modernist masters T.S. Elliot and E. Pound. Kostetskyi’s reputation of audacious “enfant terrible” of the Ukrainian literary emigration is connected with his concept of “Ukrainian realism of the 20th century” represented by him at the MUR congress in 1945. Kostetskyi eagerly tried to realize the pattern of “Ukrainian realism of the 20th century”, being the ‘pen-name’ of the Ukrainian model of modernism, in his creative work. The article analyzes some existential ideas, the problems of ethic imperative and duality, the system of modernist poetical means (deformations of time and space, phantasmagoric and hallucination motives, obscurity) in stories by I. Kostetskyi “The Cost of Human Name”, “Divine Lie”, “Whole World Belongs to You”; game component, the author’s “deliberate shocking effect” in the novel “The Saint's Day”. The absurdist origin (“Non-Saint Anthony’s Temptation”), sliding narrative planes, the method of interchanging characters, blurriness of moral estimations (“Twins will Still Meet”, “Action about Great Man”) are reflected in the plays. Прослеживается путь преобразования русскоязычного начинающего литератора Игоря Мерзлякова в Игоря Костецкого, признанного в европейском литературном мире украинского писателя. Проведён анализ выдвинутой Костецким на съезде МУРа в 1945 г. концепции “украинского реализма ХХ столетия”, с которой связана его репутация enfant terribl украинской литературной эмиграции, также экзистенциальных идей, проблемы двойничества, системы модернистских средств поэтики в рассказах и пьесах Костецкого.